WOMEN - WRITERS IN ENGLISH LITERATURE - Student of CSPU The English language theory and practice department Tojiyeva Sevinch Anvar qizi Scientific advisor: Kenjayeva Muxlisa Baxodir qizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This research delves into the crucial role of female writers in shaping English literature. By analyzing their works, we aim to uncover valuable insights that can enhance the teaching of English literature, making it more inclusive and relevant. Examining the literary contributions of women from around the globe will illuminate the evolving landscape of women's rights and their increasing participation in public life. Keywords: Awaiyar, female poets, eras and genres, psychological realm, women’s experiences women’s agensy, the historical record, Bengali novels.